1989
DOI: 10.1063/1.343172
|View full text |Cite
|
Sign up to set email alerts
|

Metal drilling with a CO2 laser beam. II. Analysis of aluminum drilling experiments

Abstract: The penetration time, crater top radius, and melted zone for aluminum plates drilled with a CO2 laser beam have been measured and analyzed on the basis of various assumptions concerning absorptivity of the liquid metal, attenuation by the metal vapor and heat exchange with the vapor. By comparison with the experimental data it is shown that each of the interaction parameters must lie within a predetermined range in order to correlate all the experimental measurements. This ascertains the reliability of the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…For laser-based cutting and drilling of aluminum, several techniques are in hand. For example, laser drilling can be carried out by the use of CO 2 lasers [1] or by applying NIR-laser irradiation in the picosecond range [2,3]. For laser pulses in the range of some nanoseconds (ns), it was shown that the ablation rate can be increased by double-pulsed ablation in the UV-, VIS-, and NIR-wavelength range [4].…”
Section: Introductionmentioning
confidence: 99%
“…For laser-based cutting and drilling of aluminum, several techniques are in hand. For example, laser drilling can be carried out by the use of CO 2 lasers [1] or by applying NIR-laser irradiation in the picosecond range [2,3]. For laser pulses in the range of some nanoseconds (ns), it was shown that the ablation rate can be increased by double-pulsed ablation in the UV-, VIS-, and NIR-wavelength range [4].…”
Section: Introductionmentioning
confidence: 99%
“…Armon et al formulated a 1-D metal drilling problem based on the enthalpy balance method and solved the problem by using the Crank-Nicholson method [5]. They also conducted an experimental investigation on metal drilling with a CO2 laser beam and analyzed the experimental results by using their theoretical model [6]. A more rigorous treatment of melt expulsion was presented by Ganesh et al [7], which employed a 2-D transient generalized model and incorporated conduction, convection and phase change heat transfer during laser drilling; this model, however, is computationally demanding.…”
Section: Introductionmentioning
confidence: 99%
“…Armon et al used the Crank-Nicholson approach to solve a one-dimensional metal drilling issue that they had developed using the enthalpy balancing method [5]. They also performed an experimental examination on CO2 laser drilling of metal, and they used their theoretical model to assess the experimental findings [6]. Ganesh et al [7], who used a two-dimensional transient generalized model and included conduction, convection, and phase change heat transfer during laser drilling, gave a more thorough study of melt expulsion.…”
Section: Introductionmentioning
confidence: 99%